Models for intra-port container terminal cooperation based on volume and vessel transfer - Pujats, Karlis; Konur, Dinçer; Golias, Mihalis (My University, 2021)
Cooperation in maritime transport is a research area that has attracted the interest of academics and practitioners. Most models published in the literature on marine container terminal cooperation focus on the planning level and consider TEUs handled at each terminal as the decision variable. At the tactical/operational level, the vessel provides a more realistic selection as the decision variable for cooperation. The objective of this paper is to analyze the impact of the choice of both decision variables for terminal intra-port cooperation. To do so, we present two main mathematical models for marine container terminal intra-port cooperation: volume-based and vessel-based models. For each model, two different cooperation schemes and seven different concession fee policies among terminals are considered. Based on the individual terminals’ before and after cooperation profits, the models are used to quantitatively assess and compare the proposed cooperation schemes and concession fee policies as well as to estimate indicators of terminals’ willingness to cooperate under each model. Results from numerical experiments using simulated data for three terminals (with high, medium, and low utilization) indicate significant differences in profit sharing and willingness to cooperate under the proposed cooperation schemes and concession fee policies between the volume- and vessel-based models.
Keywords: Port cooperation; container terminals; maritime; port operations